PENGARUH MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR PADA PELAJARAN DESAIN GRAFIS TERHADAP MINAT BELAJAR SISWA - Fricticarani, Ade; Dayurni, Popi; Abdala, Muhamad Iqbal (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This research aims to determine the effect of Smart Apps Creator-based learning media in graphic design lessons on students' learning interest. This research uses a Quasi-Experimental quantitative research method. Based on the research results, it can be concluded that the influence of Smart Apps Creator-based learning media on graphic design lessons is moderate, namely with a gain index of 0.63, the influence of conventional learning media is included in the medium criteria, namely with a gain index of 0.54 and increased learning outcomes with Smart learning media. Apps Creator is better than increasing learning outcomes from conventional learning media in graphic design lessons in Class XI MA Al-Khairiyah Pipitan Serang. Based on the results of the t test from the average value of students' learning interest, tcount > ttable (8.952> 2.02809), and the significance value (P) is <(0.05), thus Ho is rejected and Ha is accepted. There is an influence of smart apps creator-based learning media on class XI students' interest in learning at MA Al-Khairiyah Pipitan Serang